1995
DOI: 10.1007/bf01578254
|View full text |Cite
|
Sign up to set email alerts
|

Contrast on T2-weighted images of the lumbar spine using fast spin-echo and gated conventional spin-echo sequences

Abstract: A prospective study in 31 patients was designed to compare contrast quantitatively using axial conventional, gated spin-echo T2-weighted (T2W) (SE) (asymmetrical echo TE 30 and 80 ms) and axial dual-echo fast spin-echo (FSE) sequences (TEeff 20 and 120 ms) to image lumbar discs, nerve roots, and cerebrospinal fluid CSF. We used two quantitative measures, percent (%) contrast and contrast-to-noise ratio (CNR), to compare the sequences. The FSE sequence had greater % contrast and CNR on the first and second echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Traditionally, and whatever the disease, 2D SE T1-WI is preferred over 2D GRE T1-WI due to a better contrast between enhancing images and background 20,21 . Conversely, GRE T1-WI is preferred when a sharp gray-white matter contrast is required or for volumetric purposes, considering that GRE has long been the only technique that allowed acquisitions and reconstructions to be performed in a limited time frame compatible with clinical practice 20,21 . However, techniques enabling 3D TSE T1-WI acquisition within a reasonable time, suitable for clinical practice, are now proposed by all MRI manufacturers, so that acquisition durations of TSE and GRE sequences are now equivalent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, and whatever the disease, 2D SE T1-WI is preferred over 2D GRE T1-WI due to a better contrast between enhancing images and background 20,21 . Conversely, GRE T1-WI is preferred when a sharp gray-white matter contrast is required or for volumetric purposes, considering that GRE has long been the only technique that allowed acquisitions and reconstructions to be performed in a limited time frame compatible with clinical practice 20,21 . However, techniques enabling 3D TSE T1-WI acquisition within a reasonable time, suitable for clinical practice, are now proposed by all MRI manufacturers, so that acquisition durations of TSE and GRE sequences are now equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, no study has compared the performance of 3D TSE T1-WI and 3D GRE T1-WI in the settings of MS. Traditionally, and whatever the disease, 2D SE T1-WI is preferred over 2D GRE T1-WI due to a better contrast between enhancing images and background 20,21 . Conversely, GRE T1-WI is preferred when a sharp gray-white matter contrast is required or for volumetric purposes, considering that GRE has long been the only technique that allowed acquisitions and reconstructions to be performed in a limited time frame compatible with clinical practice 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…More cord lesions were depicted and higher degrees of confidence were recorded from both readers, reflecting improved image quality. Previous studies have explored the use of heavier T2 weighting in the lumbar spine [4,5], the impact of varying the different FSE parameters [6] or comparisons of dual-echo FSE and CSE where FSE was considered adequate but not better [3]. Whereas most neuroradiologists would not relinquish the proton-density image in brain imaging, the amount of information exclusively available from this image in the spine is minimal.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3D TSE and 3D gradient echo with volume interpolated sequences (VIBE by Siemens, LAVA‐Flex by GE, THRIVE by Philips, 3D Quick by Canon, and TIGRE by Hitachi) are also frequently used for brain MRI simulation. Studies have also shown superior tumor contrast and neuroradiologist rating for 3D TSE sequences compared with 3D IR‐GRE and 3D gradient echo with volume interpolated sequences 96–99 . However, 3D sequences may not be available for all sequences and scanners.…”
Section: Methodsmentioning
confidence: 99%